Forensic Assistance Project: Consultant Report 1999-021 Bugojno II Federation Commission on Missing Persons - Croat Side - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Drayer, Francine On 26-27 May 1999 the Federation Commission on Missing Persons - Croat side exhumed 27 sets of remains from five sites in the Bugojno area. According to witnesses, Croatian prisoners buried all of these individuals in 1993. The reason for the exhumations were to identify the bodies, determine cause of death, and return the bodies to the families for proper burial. Place of Exhumation: Bugojno Exhumation Site: Gračanica Area, Čipuljić Cemetery, Sultanovići Cemetery, Čaušlije Cemetery, Bristovi Cemetery Date of Exhumation: 26-27 May 1999 Minimum Number of Exhumed Individuals: 027